Ancient apocalypse end of a civilization - Page, Cynthia; Peck Danielle; Cecil, Jessica; Bookbinder, Alan (BBC Worldwide Limited, 2004)
"Traditionally, the disappearance of several ancient civilizations has been left to the theologians and historians to explain. Now the scientists have entered the fray. In this series geologists and climatologists explain their findings."